Accuracy of Coronal Plane Mechanical Alignment in a Customized, Individually Made Total Knee Replacement with Patient-Specific Instrumentation - Levengood, Gary A.; Dupee, Jack (The Journal of Knee Surgery, 2018)
The objective of this study was to evaluate the accuracy of a customized individually made total knee implant used in conjunction with patient-specific cutting guides in restoring coronal plane mechanical axis alignment using computer-assisted surgery (CAS). A consecutive series of 63 total knee arthroplasty (TKA) patients were prospectively measured with intraoperative CAS. The patient-specific instruments and implants were created utilizing a preoperative CT scan. CAS system was used for all patients, to determine mechanical alignment. Bone cuts were made using the patient-specific instruments. Both bone cuts and final coronal mechanical alignment were recorded utilizing the navigation system for the assessment.The patient-specific instruments and implants provided perfect neutral coronal mechanical alignment (0°) in 53 patients. The remaining 10 patients had a postoperative alignment within ± 2° of neutral. The average preoperative deformity was 5.57° versus 0.18° postoperatively (p < 0.0001). The mean correction angle was 5.68°. No patients had postoperative extension deficits as measured with CAS (7.50° pre-op for 40/63 patients). Customized, individually made total knee implant with patient-specific cutting jigs showed results that are comparable to those of CAS systems in this study. This technology restores the neutral coronal mechanical axis very accurately, while offering unique benefits such as improved implant fit and restoration of the patient's J-curves, which require further investigation.
Keywords: customized knee implant; mechanical alignment; patient-specific instruments; computer-assisted surgery; total knee arthroplasty